Recent advances in cervical cancer treatment: Innovations from early-stage to advanced disease - Lin, Hao; Wu, Chen-Hsuan; Fu, Hung-Chun; Ou, Yu-Che (Taiwanese journal of obstetrics & gynecology, 2025)
This article provides a comprehensive review of recent advancements in cervical cancer treatment, highlighting significant breakthroughs in managing the disease at various stages. Traditional treatments, such as radical surgery for early-stage disease and concurrent chemoradiation (CCRT) for advanced stages, have dominated clinical practice for decades. However, recent phase III studies have challenged these norms, leading to new treatment paradigms. For early-stage cervical cancer, the LACC trial revealed that minimally invasive surgery results in poorer outcomes compared to open surgery, prompting updates in clinical guidelines. Additionally, the SHAPE trial suggested that simple hysterectomy might be sufficient for low-risk cases, offering comparable oncological outcomes with fewer complications than radical hysterectomy. In locally advanced diseases, the INTERLACE study demonstrated the benefits of adding short-course induction chemotherapy before CCRT, improving progression-free and overall survival rates. Immunotherapy has also emerged as a promising treatment, with trials like KEYNOTE-A18 showing that pembrolizumab combined with CCRT enhances progression-free survival in high-risk cases. For recurrent or metastatic cervical cancer, the KEYNOTE-826 trial highlighted the efficacy of pembrolizumab with chemotherapy, showing significant survival benefits across various patient subgroups. The antibody–drug conjugates tisotumab vedotin and trastuzumab deruxtecan also showed promising results, even if patients have progressed after multiple lines of treatment including immunotherapy. These advances represent a shift towards more personalized and effective treatments for cervical cancer, improving outcomes for patients across different disease statuses.